Analytical Family Demography - Schoen, Robert; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
In this book new mathematical and statistical techniques that permit more sophisticated analysis are refined and applied to questions of current concern in order to understand the forces that are driving the recent dramatic changes in family patterns. The areas examined include the impact of the evolving Second Demographic Transition, where complex patterns of gender dynamics and social change are re-orienting family life. New analyses of marriage, cohabitation, union dynamics, and union dissolution provide a fresh look at the changing family life cycle, emerging patterns of partner choice, and the impact of union dissolution on the life course. The demography of kinship is explored, and the importance of parity progression to the generation of the kinship web is highlighted. The methodology of population projections by family status is examined, and new results presented that demonstrate how recognizing family status advances long term policy objectives, especially with regard to children and the elderly. This book applies up-to-date methods to examine the demography of the family, and will be of value to sociologists, demographers, and all those who are interested in the family.
1. Robert Schoen: Introduction -- Part One: Analyzing Theories of Family Demography: 2. Elwood Carlson: Reformulating Second Demographic Transition Theory -- 3. Máire Ní Bhrolcháin and Éva Beaujouan: Do people have reproductive goals? Constructive preferences and the discovery of desired family size -- 4. Benoît Laplante, Joice Melo Vieira, and Graziela Cristina Farina Ramos Ribeiro Barnabé: Consensual union and marriage in Brazil, 1970-2010: Gender equality, legal issues, and social context -- Part Two: At the Analytical Frontier: 5. Nicola Barban and Maria Sironi: Sequence analysis as a tool for family demography -- 6. André Grow and Jan Van Bavel: Agent-based modeling of family formation and dissolution -- 7. Rhiannon A. Kroeger and Daniel A. Powers: Examining same-sex couples using dyadic data methods -- Part Three: Analytical Applications: 8. Robert Schoen: Parity progression and the kinship network -- 9. Robert Schoen: On the implications of age-specific fertility for sibships and birth spacing -- 10. J. Bart Stykes and Karen Benjamin Guzzo: Multiple-partner fertility: Variation across measurement approaches -- 11. Richard Gisser and Dalkhat Ediev: Having ancestors alive: Trends and prospects in ageing Europe -- Part Four: Analytical Overviews: 12. Nico Keilman: Family projection methods: A review -- 13. Daniel T. Lichter and Zhenchao Qian: The study of assortative mating: Theory, data, and analysis.
Keywords: Demography; Population; Social sciences -- Statistical methods; Mathematics; Social sciences; Population and Demography; Statistics in Social Sciences, Humanities, Law, Education, Behavorial Sciences, Public Policy; Mathematics in the Humanities and Social Sciences